THE THEORETICAL ANALYSES OF THE DEFINITION OF "PSYCHOLOGICAL CORRECTION" AND IT’S ROLE AND PLACE WITHIN THE SYSTEM OF THE MORAL-PSYCHOLOGICAL SUPPORT OF THE ARMED FORCES OF UKRAINE - Belichenko, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The issue of psychological support to military personnel especially in the course of the conduct of combat activities is exceptionally up to date. One of the many ways of providing such assistance is the psychological correction. Civil psychologists in the course of their professional activity fully use the opportunities of the psychological correction whilst working with clients. In the context of providing psychological support within the Armed Forces of Ukraine this category has been slightly pushed out. This could be related with several reasons that urge for a separate analysis and highlight. This article presents a thorough theoretical analysis of the concept of psychological correction and its role and place within the system of the moral-psychological support of the Armed Forces of Ukraine. The guidelines that present the definitions of psychological correction have been analyzed and this created the possibility to identify the two existing directions of psychological correction, namely the annihilation of the negative consequence of participating in combat activities (within the framework of conducting the measures of psychological rehabilitation) and forming the qualities needed for military service (within the framework of the everyday psychological support of service activities) and additional suggestions in terms of directions of its use. The principle differences of such definitions as "psychological correction" "psychological consultation" and "psychotherapy" have been defined. The approaches on determining the psychological correction by civil researchers have been defined, both by foreign and domestic scientists. Such an analysis has allowed developing a unique definition of psychological correction and most certainly whilst including the peculiarities of the activity of military psychologists. The results of the conducted activities that have been highlighted in the article are the fundament for conducting further activity with the issues mentioned, particularly the ability to develop the methodology of using the psychological correction at every of the mentioned stages whilst working with military personnel, as well as the development of an educational program for psychologist-officers and the employees of the Armed Forces of Ukraine to increase their professional qualification in such an important issue.